On the Theory of The Symbiosis of Emotion and Reason of Xunzi - Baohong, Wu (Literary Studies, 2020)
In Xunzi's thought, the noumenon self is the existence which is connected with all things on the basis of Dao. It is the existence of the integrity of emotional desire, intellectual ability, willpower and social behavior ability. Therefore, the pursuit of emotional desire or intellectual rationality can not achieve the real self. The realization of self is the same process as people's understanding of Tao. It is not natural. It needs to eliminate the rudimentary and accumulate the etiquette and righteousness to support emotion. Therefore, Xunzi's negation of the attitude and behavior of only obeying the sexual desire and the emphasis on the hypocrisy of the way of doing Li and Yi by heart are aimed at highlighting the fact that the ontological self remains to be completed and the existence of individual life coexists with emotion and reason.